Professor Lei Zheng: Multidisciplinary management for pancreatic cancer - Seliman, Helen (HepatoBiliary Surgery and Nutrition, 2014)
Lei Zheng, MD. (Figure 1), Assistant Professor of Oncology and Surgery in the Johns Hopkins Hospital, trained in the Peking Union Medical College Beijing in 1996 and the University of Texas Medical School at San Antonio in 2000. Dr. Zheng is one of the lead researchers on a project to use immunized sera from vaccinated patients to identify candidate pancreatic cancer associated proteins against which the immune system has been activated. Through this project, he has identified a molecular pathway that underlies the tumor-stroma interaction in the tumor microenvironment of pancreatic cancer. His current research interest is to further explore the roles of the pancreatic tumor microenvironment in developing immune tolerance and in supporting tumor growth, invasion and metastasis. He is also the lead investigator on the development of vaccines and immune based therapies as pre-operative, post-operative, and long-term maintenance treatments for patients with pancreatic cancer. His clinical research interest is focused on developing multidisciplinary therapeutics in the pre-operative/neoadjuvant setting for patients with pancreatobiliary cancer.